Sanksi Pidana terhadap Tindak Pidana Korupsi Dana Hibah - I Wayan Agus Yudana; I Nyoman Sujana; Anak Agung Sagung Dewi (Jurnal Preferensi Hukum, 2020)
Corruption of subsidy funds is common in the community and is often heard through the media and news in various places. These grants often cause various problems, especially those arising from the Regional Budget (APBD), both during implementation and management or payment. There is a lot of abuse of subsidized funds for personal gain. In accordance with the background description, this research focused on the elaboration of the regulation regarding the criminal act of corruption of grant funds and the description of criminal sanctions against perpetrators who commit criminal acts of corruption of grant funds. This study was designed using a type of normative research, and the data was collected from literature studies and positive laws that apply. In case Number: 32 / Pid.Sus.TPK / 2016 / PN.Dps the defendant with the initials IWB had actually committed corruption in the grant funds according to the law in force, henceforth the Panel of Judges sentenced them to one year imprisonment and paid compensation fifty million rupiah. If he did not pay the fine, it would be replaced with a 1-month prison term and he would have to return the state money worth three hundred and fifty million rupiah. After the analysis was done, it can be concluded that according to the provisions of Article 2 and Article 3 of Law 20 of 2001, the prison sentence may be imposed on the perpetrators of the crime of grant funding.